2001
DOI: 10.1038/sj.onc.1204451
|View full text |Cite
|
Sign up to set email alerts
|

The hepatitis B virus HBx protein induces adherens junction disruption in a src-dependent manner

Abstract: Chronic hepatitis B virus infection is strongly associated with the development of hepatocellular carcinoma (HCC). Epithelial tumors are frequently characterized by loss of cadherin expression or function. Cadherindependent adhesion prevents the acquisition of a migratory and invasive phenotype, and loss of its function is itself enough for the progression from adenoma to carcinoma. The HBx protein of hepatitis B virus is thought to contribute to the development of the carcinoma, however, its role in the oncog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 41 publications
3
61
0
Order By: Relevance
“…Alternatively, or in addition, the finding that activated bcatenin turns on the expression of genes that upregulate the expression of Slug, may provide another pathway whereby E-cadherin is suppressed in HBxAg-positive cells (Nelson and Nusse, 2004). The finding that HBxAg stimulates src signaling, which disrupts E-cadherin/ b-catenin complexes (Lara-Pezzi et al, 2001c), is yet another way that HBxAg may disrupt E-cadherin function. Whatever the mechanism(s), it is clear that HBxAg mutants that fail to suppress E-cadherin, stimulate b-catenin (Figure 6), but fail to stimulate the mobility of HepG2 cells ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, or in addition, the finding that activated bcatenin turns on the expression of genes that upregulate the expression of Slug, may provide another pathway whereby E-cadherin is suppressed in HBxAg-positive cells (Nelson and Nusse, 2004). The finding that HBxAg stimulates src signaling, which disrupts E-cadherin/ b-catenin complexes (Lara-Pezzi et al, 2001c), is yet another way that HBxAg may disrupt E-cadherin function. Whatever the mechanism(s), it is clear that HBxAg mutants that fail to suppress E-cadherin, stimulate b-catenin (Figure 6), but fail to stimulate the mobility of HepG2 cells ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro analyses using HBx-overexpressing cell lines have shown that the overexpression of HBx increases its mobility associated with HCC progression. HBx down-regulates E-cadherin (33,34) and up-regulates MMPs (35,36), thereby enhancing the cell mobility and eventually increasing the malignant phenotype of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…62 HGF effects include a decrease and redistribution of VE-cadherin (which participates in intercellular contacts), ␤-catenin, and plakoglobin (linking molecules between VE-cadherin and the actin cytoskeleton) in ECs. Additionally, viral proteins may also play a role in inducing a disruption of interendothelial junctions 81 through mechanisms involving Src kinases, molecules required for vascular permeability during angiogenesis. 82 Binding between ECs and the ECM may be altered in the livers of chronic viral hepatitis patients.…”
Section: -12 Dmentioning
confidence: 99%